Pengembangan Media Big Book untuk Meningkatkan Kemampuan Berbicara Anak Usia 4-5 Tahun - Iftitah Ainur Rizki; Fahruddin Fahruddin; Ika Rachmayani; Baik Nilawati Astini (Indonesian Publication Center, 2021)
This research was motivated by the low speaking ability of children aged 4-5 years in the Mekar Sari Perumnas Kindergarten. The formulation of the problem is how is the development of big book media that can improve the speaking ability of children aged 4-5 years. The purpose of this research is to find out how the development of big book media that can improve the speaking ability of children aged 4-5 years. in the Mekar Sari Perumnas Kindergarten. This type of research is development research which consist of planning, implementing, observing and reflecting. The research subjects were five children aged 4-5 years in the Mekar Sari Perumnas Kindergarten. Methods of data collection in this study using the method of observation, and documentation. The data analysis technique in this research was descriptive qualitative. The research used two stages of development with four meetings. The results obtained at the development stage I (meeting I) obtained a percentage value of (44,29%). there was an increase in stage I (meeting II) by (60,71%), at development stage II (meeting III) it increased again to reach (72,50%), at development stage II (meeting IV or last) of (82,86%). So, it is highly recommended for parents or teachers to be able to develop media that can improve children’s speaking ability, for example, such as big book.